Avaliação do impacto do programa Bolsa Família na saúde de gestantes e mulheres com filhos menores de 1 ano em duas capitais brasileiras - Silva, Joanna D’arc Gomes Rodrigues da (2021)
The Bolsa Família Program (PBF) was a national conditional cash transfer program, aimed at poor and extremely poor families, with the objective of immediate poverty reduction. This study evaluated the impact of the PBF on Food Insecurity (FA), quality of life and anxiety in women of childbearing age in two capitals with different levels of socioeconomic development, João Pessoa/PB and Brasília/DF. This is a cross-sectional study with pregnant women and women with children under 1 year, users of the Unified Health System. Data collection was carried out between 2019 and 2020. Socioeconomic characteristics were investigated. To assess the AI, the EBIA was applied. Anxiety was assessed by IDATE-T and IDATE-E. Quality of life was measured using the WHOQOL-bref. Descriptive analyzes were performed using Pearson's chisquare test and Student's T test. There were 1382 women interviewed, in Brasília 43.7% claimed to be students/housewives and in João Pessoa 35.7% of the women were unemployed. . When comparing the groups within each city, differences were observed in terms of education, having a partner, income, occupation and number of residents per household. By limiting the maximum per capita family income, in Brasília, it was observed that despite the difference in income between the groups, the total quality of life scores maintained similarities between beneficiary and non-beneficiary women (17.4 vs 17.9), however women with lower income had higher anxiety scores (45.7 vs 43.0). In João Pessoa, an opposite behavior was observed in relation to anxiety and total quality of life outcomes: even with non-beneficiary women having an average monthly per capita income higher than that of beneficiaries, the mean anxiety scores were similar (39.38 vs. 38.5). The total quality of life showed differences between the groups, up to the maximum per capita income limit of R$ 600.00. At this point, the mean quality of life scores became similar. The AI showed a similar pattern in the two municipalities, showing that there is a clear difference in the frequencies of security and the different levels of food insecurity due to the difference in average per capita family income. This work demonstrated the importance of the PBF to reduce AI, improve quality of life and reduce anxiety in women during their reproductive cycle, pregnant women and women with children under one year of age.